Work and family: role-identity variations among Malay ethnic / Azelin Aziz...[et al.] - Aziz, Azelin; Chew Abdullah, Nor Azimah; Ku Ishak, Awanis; Mustafa Kamil, Bidayatul Akmal (Universiti Teknologi MARA, Kedah, 2019)
Work-family life provides different experiences for societies around the world. Scholars have attributed these variations to the cultural differences that exist between each group of these societies. For example, the societies in the west and east, or even ethnic groups have their own culture, causing the work-family experience to be different. However, cultural differences (e.g. role-identity) are believed to exist not only between societies but also within the society itself. This study aims to find empirical evidence that variations in role-identity are present among respondents in a shared cultural group - using the Malay ethnic as a proxy of the study. Specifically, this study examined the differences in role-identity among Malay ethnic respondents in different age categories. The results of this study confirm that variations in role-identity are indeed present within the cultural group.